THE VASCULAR RISK FACTORS ASSOCIATED WITH ANTIPLATELET RESISTANCE IN ISCHEMIC STROKE PATIENTS - TASLIM PINZON, RIZALDY; MARCHELLIA WIJAYA, BULAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: This research is to measure the prevalence rate of antiplatelet resistance in ischemic stroke patients and measure the vascular risk factors associated with antiplatelet resistance in patients with ischemic stroke. Methods and Subjects: This was a cross-sectional study with the number of respondents in this study amounted to 155 patients who all had ischemic stroke disease at Bethesda Hospital in Yogyakarta Indonesia used stroke registry to complete the data of the risk factors. VerifyNow method is used to measure the responsiveness of antiplatelet therapy. Results: Among the 155 patients with ischemic stroke, 45 were women (29%), 110 were men (71%), and the elderly (age more than 60 years old) in 81 patients. In total 155 patients with ischemic stroke, 106 of them have hypertensive, with diabetes are 19 patients, dyslipidemia is 90 patients, and ischemic heart disease in 13 patients. The prevalence of antiplatelet resistance in risk factors, for age more than 60 years, is 21 patients (25%, RR=1.06, *p=0.96), in diabetes is 7 patients (36%, RR=1.17, **p=0.74), dyslipidemia is 19 patients (21%, RR=0.68, ***p=0.24), and ischemic heart disease is four patients (30%). Among 127 patients, 22% (28 patients) had aspirin resistance, while from 42 patients, 26.2% (11 patients) were resistant to clopidogrel. Conclusion: Antiplatelet resistance is common in ischemic stroke patients. One of five patients treated with antiplatelet showed non-responsiveness. Vascular risk factors do not increase the risk of antiplatelet resistance in ischemic stroke patients.